Filozoﬁa polityczna a racja stanu. Część 2: Od dominacji normatywnego uniwersalizmu do eliminacji partykularnego empiryzmu. Normatywność i polityczność zanikającego państwa - Rau, Zbigniew (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Reason of state understood as the reason for its existence and expressed by a synthesis of the normative as well as the political, including its normative and empirical, universal and particular, abstract and concrete dimensions requires a justiﬁcation by political philosophy. Yet, in the output of the main body of Western political philosophy, including the Aristotelian, Marxist, and liberal traditions, the reason of state lacks any validation. In those traditions, there is no distinction between the elements to be found in all states and those present only in some of them. In fact, both in Aristotle and Marx, the normative in the conduct of all states sets the limits of the empirical which expresses their real behavior. The normative of general principles outlines the political of concrete states. The normative supervises the political and the political is to conﬁrm the normative. Thus, in Aristotle and Marx, the political is to indicate the necessity of the normative, its power of inﬂuence and complex character. In turn, the modern as well as contemporary liberals, especially contractarians, completely deprive their normative argument of any empirical conﬁrmation. Thus, they consciously and purposefully give it exclusively a normative dimension. Accordingly, the normative fully replaces the empirical which leads to the elimination of the political. In his concept of public reason, Rawls goes even further and considers the empirical identical with the normative, and consequently the political with the normative. For some of his followers, the irrevocable character of the connection between the normative and the empirical in the notion of public reason is to be guaranteed by elimination of the political. This is to be achieved by the abolition of the state itself and thus the deprivation of the idea of reason of state of any conceptual foundation. However, both in Montesquieu and Burke, there is a strong distinction between what characterizes all states and what distinguishes each of them. Such a distinction results from the diﬀerence between what is common to their subjects or citizens and the societies they create, and what distinguishes them from themselves and their societies. At the same time, Montesquieu’s liberalism and Burke’s conservatism oﬀer an equilibrium of the normative and the political which in turn constitutes a doctrinal support for the concept of reason of state beyond the main traditions of western political philosophy.
Keywords: racja stanu; ograniczenia wolności; demokracja; polityczność; normatywność; państwo; autorytaryzm